Action of Dicumarol on Glucosamine-1-Phosphate Acetyltransferase of GlmU and Mycobacterium tuberculosis - Han, Xiuyan; Chen, Changming; Yan, Qiulong; Jia, Liqiu; Taj, Ayaz; Ma, Yufang (Frontiers in Microbiology, 2019)
Mycobacterium tuberculosis is one of most pathogenic microorganisms in the world. Previously, the bifunctional enzyme GlmU with glucosamine-1-phosphate acetyltransferase activity and N-acetylglucosamine-1-phosphate uridyltransferase activity has been suggested as a potential drug target; therefore, discovering compounds targeting GlmU acetyltransferase is necessary. The natural products were tested for inhibition of GlmU acetyltransferase activity. We found that dicumarol exhibited inhibitory effects on GlmU acetyltransferase, with a concentration achieving a 50% inhibition (IC50) value of 4.608 μg/ml (13.7 μM). The inhibition kinetics indicated that dicumarol uncompetitively inhibited acetyl CoA and showed mixed-type inhibition for glucosamine-1-phosphate (GlcN-1-P). The activity of dicumarol against M. tuberculosis H37Ra was evaluated with a minimum inhibitory concentration (MIC) value of 6.25 μg/ml (18.55 μM) in the Alamar blue assay. Dicumarol also exhibited inhibitory effects on several clinically sensitive M. tuberculosis strains and drug-resistant strains, with a range of MIC value of 6.25 to >100 μg/ml. Dicumarol increased the sensitivity of anti-tuberculosis drugs (isoniazid and rifampicin) when dicumarol was present at a low concentration. The transcriptome and proteome data of M. tuberculosis H37Ra treated by dicumarol showed that the affected genes were associated with cell wall synthesis, DNA damage and repair, metabolic processes, and signal transduction. These results provided the mechanism of dicumarol inhibition against GlmU acetyltransferase and M. tuberculosis and also suggested that dicumarol is a potential candidate for TB treatment.